Ion‐to‐neutral ratio of 2, 5‐dihydroxybenzoic acid in matrix‐assisted laser desorption/ionization. (15th April 2013) - Tsai, Ming‐Tsang; Lee, Sheng; Lu, I‐Chung; Chu, Kuan Yu; Liang, Chi‐Wei; Lee, Chih Hao; Lee, Yuan T.; Ni, Chi‐Kung
Abstract : RATIONALE: In most previous studies, the ratios of desorbed ions and neutrals from matrix‐assisted laser desorption/ionization (MALDI) were measured outside the common MALDI conditions. In this work, we measured the ratios under common MALDI conditions. METHODS: Ions were detected using a time‐of‐flight mass spectrometer in combination with a time‐gated ion imaging detector. Mass‐resolved desorbed neutral molecules at different angles and velocities were measured using a modified crossed molecular beam apparatus. RESULTS: The upper limit of the ion‐to‐neutral ratio from pure 2, 5‐dihydroxybenzoic acid (25DHB) is 4 × 10 −9 at laser fluence 40 J/m 2, it increases to 3 × 10 −7 at laser fluence 250 J/m 2 . The ratios of matrix from the mixture of 25DHB and analyte remain in the same order of magnitude as pure 25DHB. However, the ratio of analyte depends strongly on the analyte. Values as large as 10 −3 –10 −4 for bradykinin and as small as <10 −8 for glycine were observed at laser fluence 100 J/m 2 . CONCLUSION: The ion‐to‐neutral ratios of 25DHB matrix measured in this work are much smaller than some of the values reported in previous work using different methods and/or under different MALDI conditions. Copyright © 2013 John Wiley & Sons, Ltd.